PENJADWALAN KARYAWAN (APLIKASI METODE CYCLICAL SCHEDULING DI LAUNDRY ZONE) - Widyo Sulistyo, Muhamad Cahyo (Profit: Jurnal Adminsitrasi Bisnis, 2018)
In this study, we will examine the use of cyclical scheduling in an effort to achieve competitive advantage. The use of cyclic scheduling systems is considered suitable because the cyclical scheduling system provides a fixed scheduling in a certain period of time. With a fixed schedule for some time, it is expected that the existing workers will be more proficient in doing their tasks. With the possibility to be transferred to another part, then a worker will have diverse expertise so that the company no longer needs to recruit more workers so that the costs that have become obstacles for small companies to progress can be suppressed. With a cyclical scheduling system, the workload that has been distributed less evenly, will become more evenly distributed because each worker will be given a work schedule that is adjusted to the number of consumer. From the results of the study, it is known that the workload of each worker is more evenly distributed, because each worker will get a day off on a day when the number of jobs is decreasing. Certainty of holidays and work schedule will make workers plan other activities outside the work. With this certainty, every change in schedule due to the personal interests of employees can be predicted more accurately.Â